Reconstruction Documentation: The City of Lar after the Earthquake 1960 - sima soleimanzade; Alireza Fallahi (مسکن و محیط روستا, 2018)
Disasters are different in terms of type, time and scope but they often create similar problems which indicates the importance of their scientific analysis and documentation for informing future reconstruction planning. One of the weaknesses of disaster studies in Iran is a lack of documentation of past reconstruction experiences. Many of these reconstruction projects are still alive, developed by their residents throughout several decades. However relevant documentation describing the processes of reconstruction and factors affecting the durability of their outcomes have rarely done, reviewed and criticized. The city of Lar in Fars province was devastated by an earthquake in 1339. The rescue and rehabilitation phases terminated within fifteen days. This phased followed by a reconstruction program, which involved the relocation of the city to a safer area. Now after passing more than five decades this city consists of two active areas: the new town - relocated city - and the old town. This article firstly seeks to document and analyze the Lar reconstruction after more than five decades; secondly, tries to provide unique features of this process and reasons for the durability of the outcome; and ultimately, tries to offer the lessons of this reconstruction to inform future plans. In order to achieve these goals, we conducted document review and fieldwork. Firstly, we analyzed existing documents, such as reports related to the earthquake and descriptions of the reconstruction processes in related books, national archives papers; reviewed newspapers published for a period of three years from the time of the accident until the end of reconstruction; conducted in-depth interviews with those involved in the reconstruction and the survivors who were present at the time of the earthquake; and documented the reconstruction process. Secondly, we evaluated this reconstruction based on sustainable reconstruction measures, defined through a review of literature and reconstruction experiences in Iran and the world. Finally, lessons learnt from this reconstruction were extracted. The findings of this study show that in this reconstruction, from the beginning the relocated city was planned to include residential areas, infrastructure, facilities and public buildings, and the budget for this relocation plan was allocated from the beginning. Following the city's geological studies, a safe place away from the faults was selected for the construction and earthquake-proof structures were used in building houses and public buildings of the city. Authorities began the reconstruction of the city with commitment and hard work. A commission composed of local dignitaries and clergymen oversaw all aspects of the reconstruction process, such as budgeting. Challenges that the program faced, including land ownership claims and religious issues were settled locally in the shortest time possible, avoiding interruption in the process. Facilitating commuting between the old and new city led to the economic rehabilitation of this market town and reinforced the sense of belonging of the people to the new city. The built houses were allocated to people for free or were sold to them. A committee of local dignitaries and reconstruction authorities decided about the allocation of houses by investigating the social and economical situations of residents.